Toxicity of Immune-Checkpoint Inhibitors in Hematological Malignancies - Hradska, Katarina; Hajek, Roman; Jelinek, Tomas (Frontiers in Pharmacology, 2021)
Immune checkpoint inhibitors (ICIs), especially those targeting the programmed-death 1 (PD-1) receptor and its ligands, have become indispensable agents in solid tumor anti-cancer therapy. Concerning hematological malignancies, only nivolumab and pembrolizumab have been approved for the treatment of relapsed and refractory classical Hodgkin lymphoma and primary mediastinal large B cell lymphoma to date. Nevertheless, clinical research in this field is very active. The mechanism of action of ICIs is based on unblocking the hindered immune system to recognize and eliminate cancer cells, but that also has its costs in the form of ICI-specific immune related adverse events (irAEs), which can affect any organ system and can even be lethal. In this article, we have reviewed all prospective blood cancer clinical trials investigating ICIs (both monotherapy and combination therapy) with available toxicity data with the purpose of determining the incidence of irAEs in this specific setting and to offer a brief insight into their management.